Evaluasi Perkembangan Usaha Masyarakat Penerima Pinjaman Dana Bergulir Melalui UPK- SPP, Di Wilayah Kecamatan Kasihan, Kabupaten Bantul, Yogyakarta - Munawaroh, Munjiati; Rimiyati, Hasnah (Jurnal Manajemen Bisnis, 2018)
This study aimed to evaluate the causes of the slow development of the women business community, although it has received a revolving loan from UPK SPP, so it can be used as an evaluation for UPK SPP (Unit of saving and loan for women community) at Bantul regency in Yogyakarta in particular, also for the Indonesian government relatedinstitution. UPK SPP conduct a revolving fund management unit of government that is allocated to provide savings and loan services to the public especially women.This study used a qualitative descriptive approach. The problems of this research are: (1) How does the Government Empowering Rural Village business Community especially for women. (2)How are the developments of the business community revolving loan recipients (3)What are supporting and inhibiting factors society business development loan recipients.Methods of collecting and analysis data in this study using interviews and technical Focus Group Discussion (FGD). Interviews were conducted with the chief executive of UPK SPP while FGD conducted with board members, facilitators and beneficiaries.The results of this study are expected to evaluate the causes of the slow development of the women business community, although it has received a revolving loan from UPK SPP. The result will be described in the fishbone diagram. The cause of the slow development of women business community could be caused by materials, methods, machines, measurements, environments, and people.